Comparative Effectiveness of Digitally and Conventionally Fabricated Occlusal Splints with Low-Power Laser Therapy in Treating Temporomandibular Disorders: Occlusal splints for TMD: fabrication and laser effects - Ghoveizi, Rahab; Habibi, Leili; Beyabanaki, Elaheh; Tavakolizadeh, Sara; Akbari, Hossein (Journal of Lasers in Medical Sciences, 2025)
Introduction: Temporomandibular disorder (TMD) is common, and occlusal splints (OSs) and low-power laser (LPL) therapy are effective conservative treatments. This study aims to compare the effectiveness of conventionally and digitally fabricated OS, with and without LPL, in treating TMD patients. Methods: Forty patients diagnosed with TMDs were randomly assigned to four treatment groups. The first group received LPL therapy in conjunction with digitally fabricated OS. The second group was treated with LPL therapy and conventionally fabricated OS. The third group received digitally made OS without LPL, and the fourth group was provided with conventionally fabricated OS without LPL. Patients’ pain levels were evaluated using a Visual Analog Scale (VAS) before treatment (pre-treatment) and at 1 week, 1 month, and 3 months post-treatment. The Association of Dental Research (IADR) scale was used to measure mouth opening and mandibular movements. Additionally, the physical characteristics of the OS were assessed over the 3-month period, including their resistance to failure, color change, and the level of patient satisfaction with the treatments. Results: There were no statistically significant differences in color change or failure rates between conventionally and digitally fabricated occlusal splints after three months (P>0.05). Likewise, patient satisfaction levels did not differ significantly between the two splint types (P>0.05). However, the conventionally fabricated splints required significantly more adjustment points and a longer delivery time (P<0.05). All four treatment groups experienced a significant reduction in pain intensity following the interventions (P<0.05). Additionally, the group receiving low-power laser therapy with digitally fabricated splints demonstrated greater improvements in all three movement parameters (P<0.05). Conclusion: The use of a combined treatment approach, involving a digitally-fabricated OS and LPL therapy could yield greater benefits for patients with TMDs in terms of pain reduction and functional improvements.